2018
DOI: 10.1103/physrevb.98.094506
|View full text |Cite
|
Sign up to set email alerts
|

Ingredients for the electronic nematic phase in FeSe revealed by its anisotropic optical response

Abstract: The origin of the anisotropy in physical quantities related to a symmetry-broken (nematic) electronic state is still very much debated in high-temperature superconductors. FeSe at ambient pressure undergoes a structural, tetragonal-to-orthorhombic phase transition at Ts 90 K without any magnetic ordering on further cooling, which leads to an ideal electronic nematicity. Our unprecedented optical results provide evidence that the low-energy excitation spectrum in the nematic phase is shaped by an important inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Therefore, an anisotropy in the charge dynamics due to (p-induced) nematicity [24][25][26][27] seems to be a generic feature in 122 iron-based superconductors even into the optimally-doped regime, similar to the dc transport properties. 15 Somehow peculiar with respect to the previously investigated underdoped 122 materials and even FeSe, [24][25][26][27][28][29] the optical anisotropy in the optimally K-doped 122 compound occurs at the much lower FIR energy scales, relevant to the superconducting gap(s) (Figs. 1a-c, 2f and 3c-e), thus excluding the involvement of bands deep into the electronic structure and possibly implying a less prominent impact of orbital ordering in the optimally doped than in the underdoped regime.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, an anisotropy in the charge dynamics due to (p-induced) nematicity [24][25][26][27] seems to be a generic feature in 122 iron-based superconductors even into the optimally-doped regime, similar to the dc transport properties. 15 Somehow peculiar with respect to the previously investigated underdoped 122 materials and even FeSe, [24][25][26][27][28][29] the optical anisotropy in the optimally K-doped 122 compound occurs at the much lower FIR energy scales, relevant to the superconducting gap(s) (Figs. 1a-c, 2f and 3c-e), thus excluding the involvement of bands deep into the electronic structure and possibly implying a less prominent impact of orbital ordering in the optimally doped than in the underdoped regime.…”
Section: Resultsmentioning
confidence: 97%
“…However, the optical anisotropy at ω 0 in FeSe displays a rather sudden drop on approaching T s from low T. We conclude that the anticipated pinduced lattice distortion above T s in FeSe may be less strongly or not obviously bound to the electronic structure as in other ironbased superconductors. 28,29 Common to both families of Counderdoped 122 and FeSe is nonetheless the persistence even at T < T c of the optical anisotropy evinced in the nematic phase, so that superconductivity develops in an electronically polarized state. [26][27][28][29] Overall, the anisotropy in the optical response at midinfrared energy scales unfolded in Ba(Fe 1−x Co x ) 2 As 2 and FeSe signals the impact of the nematic phase to all iron d orbitals (squeezed in energy by correlation effects) and highlights the relevance of the orbital degree of freedom, as advanced by photoemission data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, because we have obtained the high quality and relatively large-size single crystal FeSe thin film samples, it now becomes possible to examine the basic physical properties of FeSe thin films via optical measurements. As a matter of fact, the optical properties of FeSe thin films or bulk materials have been measured via conventional optical experiments [14]- [17]. Nakajima et al [16] reported the optical properties of FeSe film on CaF 2 substrate.…”
Section: Introductionmentioning
confidence: 99%